Public sector strategy design theory and practice for government and nonprofit organizations - McNabb, David E.; Lee, Chung-Shing (New York Routledge, 2021)
Within the public sector, strategies are not designed to influence markets, but instead to guide operations within a complex environment of multilateral power, influence, bargaining, and voting. In this book, authors David McNabb and Chung-Shingh Lee examine five frameworks public sector organization managers have followed when designing public sector strategies. Its purpose is to serve as a guide for managers and administrators of large and small public organizations and agencies. This book is the product of a combined more than sixty years of researching, teaching and leading organizational seminars on the theory and practice of management applications in industrial, commercial, nonprofit and public sector organizations.

The book consists of four sections: Strategic Management and Strategy Fundamentals; Frameworks for Designing Strategies; Examples of Public Sector Strategies; and Implementing Strategic Management. Throughout, the focus is on the widespread value of strategic management and adopting the strategy appropriate for the organization. Including chapters on game theory, competitive forces, resources-based view, dynamic capabilities, and network governance, the authors demonstrate ways that real managers of public sector and civil society organization have put strategic management to work in their organizations. This book will be of interest to both practicing and aspiring public servants"
Part I Strategic Management and Strategy Fundamentals. -- Chapter 1 Introduction. -- Chapter 2 Strategy Fundamentals. -- Chapter 3 Strategy Design in the Public Sector. -- Part II Frameworks for Designing Strategy. -- Chapter 4 The Competitive Forces Framework. -- Chapter 5 The Resource-Based Framework. -- Chapter 6 The Dynamic Capabilities Framework. -- Chapter 7 Network Management Framework. -- Chapter 8 The Game Theory Framework. -- Part III Public Sector Strategies. -- Chapter 9 Strategy Design and Strategic Orientation. -- Chapter 10 Innovation Strategies. -- Chapter 11 Public Sector Sustainability Strategies. -- Chapter 12 Performance Management Strategies. -- Chapter 13 Organizational Transformation Strategies. -- Part IV Implementing Strategic Management. -- Chapter 14 Strategic Management to Work. -- Chapter 15 Strategic Planning Refresher. -- Bibliography. -- Index.
ncludes bibliographical references and index.
Keywords: Public administration; Strategic planning; Administrative agencies -- Management